DEVELOPING A CULTURE OF MINDFUL LEARNING: CHALLENGES, BENEFITS, AND OPPORTUNITIES - Ročāne, Maija; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Learning is an individual process for each student. People can be aware of own learning or do not think about it at all in the diverse situations of life. However, in the pedagogical reality, the awareness of students' learning is essential as it contributes to self-regulation of behaviour and self-reflection of actions, striving towards continuous self-development. It is important to be aware of oneself mentally and physically, understanding and accepting own thoughts or feelings. The integration of all areas of personal development becomes relevant, as changes in one area are linked to changes in another. Awareness of own learning directs the learner towards the social, emotional and academic dimension, including not only awareness of the knowledge and acquired skills, but awareness of own goals, motivations, emotions, interests, the personal relevance of the learning content and also the variability of the current situation, strategies for future learning, and other elements of the learning process. Mindfulness can also be seen as a powerful 'antidote' to common mental health problems, e.g. fatigue, exhaustion, apathy, anxiety and difficulty in concentrating.  Mindfulness practices can be implemented at schools as an element of the lesson, but it is also important to purposefully create a culture of mindfulness at the institutional level, which can be greatly facilitated by the professional development of teachers. Mindfulness is a mental state of being reflective in the present moment. It provides the ability to live intensely in the present moment, acceptance of own thoughts and feelings, a sense of perspective and the ability to cope with stressful situations through conscious concentration. The aim of this publication is to analyze the theoretical aspects of mindfulness, the possibilities of facilitating the learning process through mindfulness practices, as well as to carry out empirical research evaluating 16-19-year-old students` self-awareness skills, the phenomenon of the presence of mindfulness in their learning process and its impact on their learning outcomes.